Jasmonate Hypersensitive 3 negatively regulates both jasmonate and ethylene-mediated responses in Arabidopsis. (11th May 2022) - Chung, KwiMi; Demianski, Agnes J; Harrison, Gregory A; Laurie-Berry, Neva; Mitsuda, Nobutaka; Kunkel, Barbara N
Abstract: Jasmonate (JA) is an important hormone involved in regulating diverse responses to environmental factors as well as growth and development, and its signalling is influenced by other hormones such as ethylene (ET). However, our understanding of the regulatory relationship between the JA and ET signalling pathways is limited. In this study, we isolated an Arabidopsis JA-hypersensitive mutant, jah3 ( jasmonate hypersensitive3 )- 1 . Map-based cloning revealed that the JAH3 gene corresponds to At4g16535 . JAH3 encodes a protein of unknown function whose amino acid sequence has similarity to leukocyte receptor cluster-like protein. The mutation in jah3-1 is caused by a single nucleotide change from A to T at position 220 of 759 bp. Using CRISPR-Cas9, we generated a second allele, jah3-2, that encodes a truncated protein. Both of these loss-of-function alleles resulted in hypersensitivity to JA, ET-induced root growth inhibition, and accelerated dark-induced senescence. Double mutant analyses employing coronatine insensitive 1 ( coi1 ) and ethylene insensitive 3 ( ein3 ) mutants ( jah3 coi1 and jah3 ein3) demonstrated that the hypersensitive phenotypes of the jah3 mutants are mediated by JA and ET signalling components COI1 and EIN3. Therefore, we propose that JAH3 is a negative regulator of both JA and ET signalling. Abstract : JASMONATE HYPERSENSITIVE 3 (JAH3) is a common negative regulator of jasmonate and ethylene signalling pathways, suppressing both jasmonic acid and ethylene-induced chlorosis and senescence-related gene expression in the dark.